2018
DOI: 10.1152/ajpendo.00070.2018
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is a significant determinant of sarcopenia in advanced kidney disease

Abstract: Maintenance hemodialysis (MHD) patients display significant nutritional abnormalities. Insulin is an anabolic hormone with direct effects on skeletal muscle (SM). We examined the anabolic actions of insulin, whole-body (WB) and SM protein turnover, in 33 MHD patients and 17 participants without kidney disease using hyperinsulinemic euglycemic euaminoacidemic (dual) clamp. Gluteal muscle biopsies were obtained before and after the dual-clamp. At baseline, WB protein synthesis and breakdown rates were similar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Most differences between patients with and without diabetes are related to body composition, with reduced lean tissue mass in patients with diabetes (Table 1). This difference in body composition is expected: insulin resistance is a significant determinant of sarcopenia in advanced kidney disease [38].…”
Section: Discussionmentioning
confidence: 95%
“…Most differences between patients with and without diabetes are related to body composition, with reduced lean tissue mass in patients with diabetes (Table 1). This difference in body composition is expected: insulin resistance is a significant determinant of sarcopenia in advanced kidney disease [38].…”
Section: Discussionmentioning
confidence: 95%
“…IR presents as a shift of the insulin concentration-effect curve towards higher insulin concentrations. IR is highly correlated with occurrence of atherosclerosis, cardiovascular risk, and progression of chronic kidney disease (CKD) (5)(6)(7)(8)(9). Hyperinsulinemic-euglycemic clamp (HEC) test and homeostatic model assessment (HOMA) are effective methods for determination of IR (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Deger et al showed that skeletal muscle protein synthesis decreased significantly in HD subjects with an insulin resistance state in patients on HD [ 40 ]. Insulin and IGF-1 have a similar pathway in muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%